2014
DOI: 10.1016/j.technovation.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of risk management practices on the performance of new product development programs

Abstract: Link back to DTU Orbit Citation (APA):Oehmen, J., Olechowski, A., Kenley, C. R., & Ben-Daya, M. (2014). Analysis of the effect of risk management practices on the performance of new product development programs. Technovation, 34(8), 441-453. DOI: 10.1016441-453. DOI: 10. /j.technovation.2013 Analysis of the effect of risk management practices on the performance of new product development programs Highlights Investigates the association between risk management practices and new product development program p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 41 publications
5
84
0
10
Order By: Relevance
“…The risks we consider in this study all have negative or undesirable consequences for the focal project, in line with standard project management practice (Maguire and Hardy 2013;Oehmen et al 2014). The outcomes that result from the decision to carry out the project are always influenced by occurring risks (Raz et al 2002), such that increasing risk impacts and risk occurrence probabilities mitigate the value of the decision to conduct the project (Dey 2012).…”
Section: Hypothesis Developmentmentioning
confidence: 91%
See 4 more Smart Citations
“…The risks we consider in this study all have negative or undesirable consequences for the focal project, in line with standard project management practice (Maguire and Hardy 2013;Oehmen et al 2014). The outcomes that result from the decision to carry out the project are always influenced by occurring risks (Raz et al 2002), such that increasing risk impacts and risk occurrence probabilities mitigate the value of the decision to conduct the project (Dey 2012).…”
Section: Hypothesis Developmentmentioning
confidence: 91%
“…It is widely acknowledged in project management literature that risks may have positive or negative effects on a project's objectives (Bryde and Volm 2009;Maguire and Hardy 2013;PMI 2008) and therefore may not only be a threat to project success, but also create opportunities (Teller et al 2014). However, project risk management processes still focus on potential negative effects (Bryde and Volm 2009;Raz et al 2002), and risks in a project management context usually refer to uncertain events with negative or undesirable consequences (Maguire and Hardy 2013;Oehmen et al 2014). Thus, it can be concluded that project risk management aims to identify uncertain events and their (predominantly negative) impact on the project for the purpose of reducing the said impact (Pich et al 2002).…”
Section: Risk Assessment and Anticipated Project Successmentioning
confidence: 99%
See 3 more Smart Citations